Slum Upgrading and Participation : Lessons from Latin America - Imparato, Ivo (Washington, DC: World Bank, 2013)
This book talks about participation, from the first to the last page. And that is its strength, for participation is a road leading to democracy. The true participation it talks about does not rely on hours of compulsory labor or imposed levies; there is nothing forced about it. Rather, it is a process in which men and women engage their will, their sense of responsibility, their abilities, their dignity. It is a vital participation, because it affects much of what makes for a better life in a poor neighborhood: water supplies, sanitation, electricity, roads, drainage, public spaces, housing. For some, participation creates risks, whether of popular protests, mismanaged conflicts of interests, or mounting expectations that are difficult to meet. But, in reality ad above all, participation creates opportunity. In favors civic learning and people's empowerment. It opens the way to alternatives. It enhances the quality of projects and the continuity of development. It enables an escape from rigid control or populist clientelism into a practice of strategies of negotiations.